Treatment of chronic hepatitis C among injecting drug users: A 5-year follow-up - Ruzić Maja; Fabri Milotka; Preveden Tomislav; Kiralj Katarina; Mikić Stefan Sandra; Vukadinov Tatjana (Vojnosanitetski Pregled)
Background/Aim. Hepatitic C infection (HCV) is a systemic, generalised disease with the prevalence of inflammation in the liver. The aim of this study was to determine the success of treatment for chronic hepatitis C with pegilated interferon alfa 2a and ribavirin in injecting drug users. Methods. This a 5-year follow-up study included 30 patients [63.3% men and 36.7% women, average age 30.2 years (SD 7.1 years)] injecting drug users in one-year abstinence, with chronic hepatitis C, treated with the pegilated interferon α 2a and ribavirin. Complete history with possible route of infection, the standard biochemical tests, liver biopsy, quantification of the viral genome in sera and HCV genotyping and subtyping were done prior to the therapy initiation. Depending on the HCV genotype, the therapy was conducted over a period of 48 weeks for genotype 1 and 24 weeks for genotype non 1. Five years later all 30 patients were invited on control examination; 22 of them appeared at the check-up and quantification of the viral genome in their sera were analized. Results. The established degree of liver fibrosis was: F0 in 40%, F1 in 23.33%, F2 in 26.67%, F3 in 3.33% and F4 in 6.67% of the patients. Genotype 3a was dominant (50.0%), 1b was registered in 40.0%, 1a in 6.66% and 2b in 3.33% of the patients. Sustained virologic response (SVR) was achieved in 86.7% of the patients, 10.0% of the patients were non-responders, while 3.33% of them revealed recurrence of HCV. Opiate abuse recurrence during antiviral therapy happened in 6.7% of the patients. Five years after the antiviral therapy 73.3% of the patients appeared at the check-up and all of them were in stable abstinence from opiate abuse. All of those, with a sustained viral response of five-year duration, had the negative PCR HCV RNA test (< 50 IU ml-1). In the patients showing unsatisfactory therapy response 5 years before, antiviral therapy was repeated by the same therapeutic regimen, but without adequate therapeutic response. A total of 26.7% of the patients were lost from the records. Conclusion. In a 5-year follow-up period 73.3% of the patients used to come regularly to check-ups and among them neither the opiate abuse recurrence nor HCV infection recurrence were registered.